When a Doctor Falls from the Sky: The Impact of Easing Doctor Supply Constraints on Mortality - Okeke, Edward N. (American Economic Review, 2023)
This paper describes the results of a policy experiment conducted in coordination with the Nigerian government. In this experiment, some communities were randomly selected to receive a new doctor. These doctors were posted to the public health center serving the community to work for a year. Prior to their arrival, health care was provided by mid-level health care providers (MLP). To separate the effect of (ostensibly higher) quality from that of quantity, another group of communities was provided with an additional mid-level health care worker. A third group of communities received no additional workers. No other inputs were provided. I find a measurable decrease in mortality in communities assigned a doctor but not in communities assigned an additional MLP, suggesting that quality in the health care sector is a significant constraint.